SOIL BULK DENSITY AS IMPORTANT MANAGEMENT FACTOR AND ECOSYSTEM SERVICES WELL FUNCTION - Alina EFTENE; Petru IGNAT; Irina-Adriana CHIURCIU; Alexandrina MANEA; Daniela RADUCU; Sorina DUMITRU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The decisions for a good soil management need many points of support to substantiate the management strategy. These support points must reflect as accurately as possible the field reality. In the present paper, these support points are the physico-chemical characteristics of two Luvisols: one, the crop soil (P1) and other under pasture (P2). The two soils had been analyzed to pointed out how soil bulk density is an important key of soil fertility and consequently of the agriculture management and how influence the well function of an important ecosystem services as the „maintenance of soil structure“. Bulk density (BD) being considered as a referential parameter, it was compared with: packing density (PD), restricting bulk density (BDr), hydraulic conductivity (HC), and organic matter (OM) as parameters used to monitoring the structure quality. The results showed low differences between PD and BD values of both profiles, while the values of BDr drop drastically into the clayey horizons, matching perfectly with the higher clay content, and showed the stressed conditions for the roots in both soils. The HC depends not only on the poral space design, but also on the quality and quantity of the clay coatings that coated the pore walls. The illuvial constituents partially clog the pores, reducing the values of the poral space (as part of BD), and hence the HC. The BD, being one of the physical quantifying characteristics (that assessing quantitatively the water and air in soil) represent an important key of soil fertility and strongly influenced „maintenance of soil structure“ecosystem service, and consequently emphasized the quality of the agriculture management. The paper management recommendations place it on a direct path that meets the problems faced by the farmers, related to the Luvisols physical and mechanical properties (unfavorable aero-hydric conditions and high energy consumption and relatively short working period) on the general background of the increasingly severe climate changes.